Analisis Kekuatan Tarik dan Tekan Cetakan Pasir akibat Variasi Ukuran Butir dan Kadar Pengikat Pasir Cetak - Sella Devianty; Ahmad Syuhri; Hari Arbiantara (ROTOR, 2014)
Molding sand is one the most important thing in sand casting. The weak tensile strength and compressive strength of molding sand causes some defects, such as sand drop and sand inclusion. Therefore this research is done by varying grain size and percentage of binder in molding sand. The purpose of this research was to analyze the tensile strength and the compressive strength of sand mold due to variation of grain size and binder presentation. Each treatment will through tensile strength test and compressive strength test, then the data from the test will be analyzed by using ANOVAfor factorial experiments with SPSS 16.0 and a significance level of 5%. From the research and analysis conducted found that the tensile strength of the molding sand is influenced by the grain size and binder presentation, meanwhile the compressive strength is influenced by the binder presentation but is not affected by the grain size. The highest average value of the sand mold tensile strength is 0.912 N/mm2 and the highest average value of the sand mold compressive strength is 2.7567 N/mm2. Those values are achieved by the use of a mixture of GFN 40-50 AFS silica with a percentage binder as much as 1.5%. Keywords: Molding sand, grain size, binder